Emissions from the Open Laboratory Combustion of Cheatgrass (Bromus Tectorum) - Rennie, Megan; Samburova, Vera; Sengupta, Deep; Bhattarai, Chiranjivi; Arnott, W. Patrick; Khlystov, Andrey; Moosmüller, Hans (Atmosphere, 2020)
Cheatgrass (Bromus Tectorum) is a highly invasive species in the Great Basin of the Western USA that is increasing the frequency and intensity of wildland fires. Though cheatgrass plays a significant role in the fire ecology of the Great Basin, very little is known about its combustion emissions. The fresh smoke from 16 open laboratory burns of cheatgrass was analyzed using real-time measurements and filter analysis. We presented measured intensive optical properties of the emitted smoke, including absorption Ångström exponent (AAE), scattering Ångström exponent (SAE), single scattering albedo (SSA), and other combustion properties, such as modified combustion efficiency (MCE) and fuel-based emission factors (EFs). In addition, we gave a detailed chemical analysis of polar organic species in cheatgrass combustion emissions. We presented EFs that showed a large variation between fuels and demonstrated that analysis of combustion emissions for specific fuels was important for studying and modeling the chemistry of biomass-burning emissions.